2012
DOI: 10.1063/1.4772774
|View full text |Cite
|
Sign up to set email alerts
|

Time evolution of nanosecond runaway discharges in air and helium at atmospheric pressure

Abstract: Time-and space-resolved fast framing photography was employed to study the discharge initiated by runaway electrons in air and He gas at atmospheric pressure. Whereas in the both cases, the discharge occurs in a nanosecond time scale and its front propagates with a similar velocity along the cathode-anode gap, the later stages of the discharge differ significantly. In air, the main discharge channels develop and remain in the locations with the strongest field enhancement. In He gas, the first, diode "gap brid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 11 publications
4
26
0
Order By: Relevance
“…This duration is consistent with the lifetime of the hot spots, whose depletion terminates the radial electric field and, therefore, terminates the radial wave of electrons. However, on the same time scale other explosive centers form somewhere else on the cathode edge, followed by a similar development of the discharge channel [16].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This duration is consistent with the lifetime of the hot spots, whose depletion terminates the radial electric field and, therefore, terminates the radial wave of electrons. However, on the same time scale other explosive centers form somewhere else on the cathode edge, followed by a similar development of the discharge channel [16].…”
Section: Discussionmentioning
confidence: 90%
“…Let us now consider a possible reason for the appearance of a short outburst of energetic electrons with a duration of 1-2 ns. The results of the recent research [16] showed existence of several resistive plasma channels in the CA gap with a lifetime of ∼ 2 ns. The evanescence of a channel is followed by generation of a new channel from a different emission center on the cathode shortly before or after the first channel ceases to exist.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations